Youtube Free Quran Education As a Source of Islamic Education Learning Materials and Media - Ashidiqi, Muna Nur Azizah; Rohmatiah, Anis; Rahmah, Febria Afia (Khalifa Journal of Islamic Education, 2019)
This study aims to analyze the animated content of YouTube Free Quran Education channel for the reference of Islamic education material and as a learning medium in the learning of Islamic Religious Education (PAI) in schools. This study uses qualitative methods with content analysis. All data was taken by taking eight videos contained in the YouTube Free Quran Education channel randomly, then continued to the identification, classification, and analysis of the contents of animated content. Overall the results of the study indicate that there are six contents of Islamic education material that can be used as material or references in the learning of Islamic Education for teachers in schools. The six materials are the education of the Qur’an, Islamic history, fiqh, aqidah, hadith and akhlaq (morality). Besides being able to be used as a reference for teachers, the YouTube Free Quran Education channel can also be used as a medium for teachers and as a support for independent learning for students at home, because all of the material can be accessed by students whenever and wherever they are.